Como o podcast pode ser uma ferramenta facilitadora no ensino e na aprendizagem da educação financeira - Lyrio, Deyse Mara Nieto (2023)
This dissertation seeks to contribute with new ideas about the use of podcasts for teaching Financial Education aimed at High school 2nd grade students class at a state public school in the city of São Mateus-ES. This research has the general objective of evaluating the possibilities of teaching Financial Education through the use of the podcast. In this research, of a qualitative nature, the methodological course initially occurred with the presentation of two questionnaires directed to the students. Then, the activity plans were handed over to develop the teaching of Financial Education using the podcast, in which the students created the script, performed the recording, editing and presentation of the podcast episodes for the other students. Learning, in view of the presentation of the suggested theme, was about the “savings account”, within the possibilities of teaching Financial Education. The results indicate that the research achieved its objective, allowing this tool to act in a very relevant way in the evolution of teaching and student learning. Even having difficulties in using the technological tool in the educational field, they felt attracted and stimulated, showing commitment the teaching and learning.